Parathyroid Hormone and the Use of Diuretics and Calcium‐Channel Blockers: The Multi‐Ethnic Study of Atherosclerosis. (15th February 2016) - Zaheer, Sarah; de Boer, Ian; Allison, Matthew; Brown, Jenifer M; Psaty, Bruce M; Robinson‐Cohen, Cassianne; Ix, Joachim H; Kestenbaum, Bryan; Siscovick, David; Vaidya, Anand
ABSTRACT: Thiazide diuretic (TZ) use is associated with higher bone mineral density, whereas loop diuretic (LD) use is associated with lower bone density and incident fracture. Dihydropyridine‐sensitive calcium channels are expressed on parathyroid cells and may play a role in parathyroid hormone (PTH) regulation. The potential for diuretics and calcium‐channel blockers (CCBs) to modulate PTH and calcium homeostasis may represent a mechanism by which they influence skeletal outcomes. We hypothesized that the use of LD and dihydropyridine CCBs is associated with higher PTH, and TZ use is associated with lower PTH. We conducted cross‐sectional analyses of participants treated for hypertension in the Multi‐Ethnic Study of Atherosclerosis who did not have primary hyperparathyroidism or chronic kidney disease ( n = 1888). We used adjusted regression models to evaluate the independent association between TZ, LD, and CCB medication classes and PTH. TZ use was associated with lower PTH when compared with non‐TZ use (44.4 versus 46.9 pg/mL, p = 0.02), whereas the use of LD and CCBs was associated with higher PTH when compared with non‐users of each medication class (LD: 60.7 versus 45.5 pg/mL, p < 0.0001; CCB: 49.5 versus. 44.4 pg/mL, p < 0.0001). Adjusted regression models confirmed independent associations between TZ use and lower PTH (β = –3.2 pg/mL, p = 0.0007), and LD or CCB use and higher PTH (LD: β = +12.0 pg/mL, p < 0.0001; CCB: +3.7 pg/mL, p < 0.0001). Among CCB users, the use of dihydropyridines was independently associated with higher PTH (β = +5.0 pg/mL, p < 0.0001), whereas non‐dihydropyridine use was not (β = +0.58 pg/mL, p = 0.68). We conclude that in a large community‐based cohort with normal kidney function, TZ use is associated with lower PTH, whereas LD and dihydropyridine CCB use is associated with higher PTH. These associations may provide a mechanistic explanation linking use of these medications to the development of skeletal outcomes. © 2016 American Society for Bone and Mineral Research.